CLASH OF WEST AND EAST CIVILIZATIONS IN QUR’AN INTERPRETATION - Ahmad Atabik (ADDIN, 2017)
This article describes the clash of west and east civilizations from the perspective of the Qur’an interpretation. As is well known that the Qur’an reveals a clash of civilizations between the West which is represented by the Roman and the east are Persian. The clash occurred for many years. This war began with the triumph of Persians, the Qur’an clearly interpreted that nine years later the Roman defeat the Persian. Roman Empire which is meant by ar-Rum is the Kingdom of Eastern Roman centered in Konstantinopel, not the Western Roman kingdom centered in Rome. The West Roman kingdom, before the events, recounted in this verse occurs has collapsed in 476 CE. The Romans are Christians (people of the scripture), and the Persians religion Majusi (idolaters).